ANALISIS PENGGUNAAN CHAT GPT (AI) DAN MODUL PEMROGRAMAN TERHADAP MOTIVASI BELAJAR DAN KREATIVITAS MAHASISWA DALAM MATA KULIAH PEMROGRAMAN PADA PROGRAM STUDI PENDIDIKAN TEKNOLOGI INFORMASI, UNIVERSITAS BINA BANGSA - Mutaqin, Reihan; Desty Endrawati Subroto; Cecep Warman (Jurnal Saintifik (Multi Science Journal), 2024)
This research aims to analyze the use of CHAT GPT (AI) and Programming Module on students' understanding of programming in the Department of Information Technology Education at Bina Bangsa University. The research method used is a descriptive quantitative approach, with questionnaires distributed to 70 students as the population, and a sample of 35 students from two classes, namely 6A and 6B, was taken. The research subjects were given questionnaires, and the data were analyzed using the Likert scale as a measurement scale. The questionnaires were distributed through the Google Form platform. The results of the research show that the use of CHAT GPT (AI) is preferred by students in classes 6A and 6B in understanding programming concepts compared to the use of Programming Module. The utilization rate of CHAT GPT (AI) reaches 93.33% in class 6A and 75.24% in class 6B, while the utilization rate of Programming Module is only 75.91% in class 6A and 88.91% in class 6B. Therefore, CHAT GPT (AI) has good potential as a learning tool to help students understand programming concepts. The research results also indicate that the use of CHAT GPT (AI) and Programming Module has a positive impact on students' understanding in the programming course.